Emotion regulation and academic performance: a systematic review of empirical relationships - Andrés, María Laura (2017)
It has been suggested that emotion regulation (ER) is a predictive factor of academic performance. However, empirical studies are scarce and relatively little is known about the specific relationships between academic performance indicators and ER strategies and skills. The goal of this study is to identify the state of the art in terms of the relationship between emotion regulation (ER) and academic performance. A systematic review of the literature was conducted through Google Scholar, ERIC and PsyArticles by combining the terms emotion regulation and emotion self-regulation with: abilities, competency, achievement, success, performance, academic learning, school, literacy, classroom, education, reading, math. Seventeen articles were selected and, following an analysis, these were divided into two groups. The first group included articles that evaluated ER strategies. In this group, experimental designs and behavioral indicators as measures of ER predominated. The second group included studies that evaluated ER skills. In this group, cross-sectional studies and self-reporting or third-party reporting measures to evaluate ER predominated. Recommendations for future research are indicated.